EFFECTS OF SUBSTRATE AND WATER AVAILABILITY ON THE INITIAL GROWTH OF Alibertia edulis RICH. - Jeromini, Tatiane Sanches; Mota, Leandro Henrique de Sousa; Scalon, Silvana de Paula Quintão; Dresch, Daiane Mugnol; Scalon, Lourenço Quintão (Floresta, 2018)
Alibertia edulis Rich. is a native species of the Brazilian Cerrado and can be used for reforestation of degraded areas. In addition, it produces edible fruits. The objective of this study was to evaluate the effect of substrates and water levels on the emergence, initial growth, and quality of seedling of A. edulis. The substrates tested were: latosol (L), latosol + sand (L + S = 1:1), latosol + sand + chicken manure (L + S1 + CM = 1:1:0,5), latosol + sand + chicken manure (L + S2 + CM = 1:2:0,5), and latosol + commercial substrate (L + C = 1:1); and the water retention capacities (WRC) tested were: 25, 50, 75, and 100%. The experiment was carried through in a completely randomized design and subdivided into a plot scheme, in which the plots represented water availability and the subplots represented the substrates. Latosol + commercial substrate at 100% of WRC provided the best conditions for emergence, initial growth and formation of seedlings of A. edulis. Sowing in the substrate Dystroferric Red Latosol isolated at 25% of WRC should not be used for the formation of seedlings of this species.